2015
DOI: 10.4161/21645515.2014.987006
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of humoral, mucosal, and cellular immune responses following co-immunization of HIV-1 Gag and Env proteins expressed by Newcastle disease virus

Abstract: The combination of multiple HIV antigens in a vaccine can broaden antiviral immune responses. In this study, we used NDV vaccine strain LaSota to generate rNDV (rLaSota/optGag) expressing human codon optimized p55 Gag protein of HIV-1. We examined the effect of co-immunization of rLaSota/optGag with rNDVs expressing different forms of Env protein gp160, gp120, gp140L [a version of gp140 that lacked cytoplasmic tail and contained complete membrane-proximal external region (MPER)] and gp140S (a version of gp140 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…An ideal HIV vaccine should not only stimulate a long-lasting neutralizing antibody response, it should also elicit strong cell-mediated immunity, particularly a CD8 + response, which is believed to play a crucial role in virus clearance [127]. With the gag and pol proteins being the most important elicitors of robust immune responses against HIV [128], attempts have been made to construct a recombinant vectored vaccine expressing these proteins. In one study, genetically engineered NDV expressing HIV gp140 or gp160 have been shown to induce a strong anti-HIV humoral immune response following parenteral or intranasal administration in mice [61].…”
Section: Engineered Ndv As a Vaccine Vector In Manmentioning
confidence: 99%
“…An ideal HIV vaccine should not only stimulate a long-lasting neutralizing antibody response, it should also elicit strong cell-mediated immunity, particularly a CD8 + response, which is believed to play a crucial role in virus clearance [127]. With the gag and pol proteins being the most important elicitors of robust immune responses against HIV [128], attempts have been made to construct a recombinant vectored vaccine expressing these proteins. In one study, genetically engineered NDV expressing HIV gp140 or gp160 have been shown to induce a strong anti-HIV humoral immune response following parenteral or intranasal administration in mice [61].…”
Section: Engineered Ndv As a Vaccine Vector In Manmentioning
confidence: 99%
“…There is no preexisting immunity to NDV in humans. NDV infects via the intranasal and oral routes and induces both mucosal and systemic immune responses (9)(10)(11)(12)(13)(14)(15)(16)(17). Previously, we demonstrated the potential of NDV as a vaccine vector for HIV-1 (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Additionally, rNDV/gp140S induced greater CD4 + and CD8 + T-cell response in mice [91]. The combination of multiple HIV antigens in rNDV vaccine vector to broaden antiviral immune responses showed that inclusion of Gag with gp160, gp140S and gp140L enhanced the level of Env-specific IFN-γ-producing CD8 + T cells in mice, and inclusion of Gag with gp160 and gp140L also resulted in increased Env-specific CD4 + T cells, indicating lack of antigen interference in a vaccine containing rNDVs expressing Env and Gag proteins [92]. Taken together, these data illustrate that rNDV expressing HIV-1 gag or Env protein is a promising vaccine candidate to elicit potent mucosal, humoral and cellular immune responses against HIV-1 infection.…”
Section: Rndv-vectored Vaccine Against Human Infectious Diseasesmentioning
confidence: 95%
“…Additionally, NDV shares only a low level of amino acid sequence identity with human viruses and is distinct antigenically, suggesting that the human population would be susceptible to vaccination with rNDV-based vectors [71]. Recent advances using reverse genetics have indeed provided a means of generating rNDV with potent vaccine vector against human infectious diseases [86][87][88][89][90][91][92][95][96][97][98][99][100]. Although studies with animal models showed that NDV expressing protective antigens of HIV, human respiratory syncytial virus, Nipah virus or SIV were immunogenic and induced protection against challenge, however, mice and guinea pigs are not good models for evaluating a host range-restricted vector against human pathogens, because their permissiveness to both the vector and the pathogen probably do not accurately reflect that of the human due to the phylogenetic distance.…”
Section: Conclusion and Future Perspectivementioning
confidence: 98%
See 1 more Smart Citation